Hopkins Syndrome in a 14-Year-Old Boy; a Case Report - Majidi, Alireza; Saket, Sasan; Nabizadeh Gharghozar, Zohreh; Akrami, Ehsan; Fayyazi, Seyed Mohsen (Archives of Academic Emergency Medicine, 2018)
Hopkins syndrome (HS) is a flaccid paralysis resembling poliomyelitis that has been seen in some children who are recovering from an acute episode of asthma. This syndrome should be suspected based on clinical findings even before the occurrence of characteristic breathing patterns and epilepsy. We report a 14-year-old boy who had experienced an episode of HS.